1999
DOI: 10.1164/ajrccm.159.1.9712068
|View full text |Cite
|
Sign up to set email alerts
|

Unopposed Neutrophil Elastase in Bronchoalveolar Lavage from Transplant Recipients with Cystic Fibrosis

Abstract: Large numbers of neutrophils with unopposed neutrophil elastase (NE) proteolytic activity are found in lower respiratory tract secretions from most patients with advanced cystic fibrosis (CF). To determine whether antielastase defenses may be overwhelmed in epithelial lining fluid after lung transplantation, we measured NE activity (cleavage of the specific substrate, MeO-Suc-Ala-Ala-Pro-Val-pNA) in bronchoalveolar lavage fluids (BALF) obtained for surveillance or diagnostic purposes at various intervals (1 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…Large numbers of neutrophils become sequestered in the airways of patients with CF in association with chronic bacterial infection [1-3,14] and neutrophils can also appear in relatively large numbers in bronchoalveolar secretions of lung transplant recipients with CF as well as those of recipients with other transplant indications as a consequence of reperfusion injury, infection, or delayed allograft dysfunction [10,15,16]. We observed that intracellular intact annexin 1 was largely deficient in neutrophils from bronchial aspirates of lung transplant patients with CF and bacterial tracheobronchitis.…”
Section: Discussionmentioning
confidence: 99%
“…Large numbers of neutrophils become sequestered in the airways of patients with CF in association with chronic bacterial infection [1-3,14] and neutrophils can also appear in relatively large numbers in bronchoalveolar secretions of lung transplant recipients with CF as well as those of recipients with other transplant indications as a consequence of reperfusion injury, infection, or delayed allograft dysfunction [10,15,16]. We observed that intracellular intact annexin 1 was largely deficient in neutrophils from bronchial aspirates of lung transplant patients with CF and bacterial tracheobronchitis.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with CF have a significantly higher risk of acquiring and harboring P. aeruginosa in the lung allograft compared with transplant recipients with other underlying diseases (2). P. aeruginosainduced inflammation may be associated with the occurrence of posttransplant bronchiolitis obliterans syndrome (BOS), leading to progressive, irreversible graft dysfunction and death (2,3).…”
Section: Colonization Of Both the Upper And Lower Airways Withmentioning
confidence: 99%
“…In fact, a peptide from human neutrophil elastase was found in pooled BOS samples. Neutrophilia has been associated with BOS [4][6], [11], [12] and generalized protease activity has been noted to increase in BOS along with a decrease in anti-protease activity [4], [12]. Our findings suggest that although other proteases are present, the neutrophil elastase is the predominant active protease.…”
Section: Discussionmentioning
confidence: 47%
“…In addition to a peribronchial infiltration of lymphocytes, neutrophilia also is a predominant finding in BOS [4][9]. These neutrophils release factors of the innate immune system, along with proteases [4], [10][12]. Despite the high incidence of BOS, the underlying pathogenesis remains unknown and no clinical biomarker has been found to predict its onset.…”
Section: Introductionmentioning
confidence: 99%